Jumping translocations, a novel finding in chronic lymphocytic leukaemia. (19th April 2015) - Miller, Cecelia R.; Stephens, Deborah; Ruppert, Amy S.; Racke, Frederick; McFaddin, Andrew; Breidenbach, Heather; Lin, Huey‐Jen; Waller, Kathy; Bannerman, Tammy; Jones, Jeffrey A.; Woyach, Jennifer A.; Andritsos, Leslie A.; et al.
Summary A jumping translocation (JT) is a rare cytogenetic aberration that can occur in haematological malignancy. It involves the translocation of the same fragment of donor chromosome onto two or more recipient chromosomes, typically in different cells. In this study, we describe the first series of chronic lymphocytic leukaemia (CLL) patients with JTs reported to date. Following a review of 878 CLL patient karyotypes, we identified 26 patients (3%) with 97 JTs. The most commonly occurring breakpoint in these translocations was 17p11.2. Loss of TP53 was identified prior to or at the same time as JT in 23 of 26 patients (88%). All patients eventually developed a complex karyotype. All but one patient has required treatment for CLL, with estimated median time to treatment of 11·5 months. This study establishes JTs as a recurrent abnormality found in CLL patients with aggressive disease. JTs contribute to complex karyotypes and, in many cases, are involved in chromosomal rearrangements that result in loss of the tumour suppressor gene TP53.